DNA Barcode of Homalomena pexa inferred from Internal Transcribed Spacer Region - Aprilianingsih, Risqi; Farhatul Wahidah, Baiq; Hariri, Muhammad Rifqi (Jurnal Riset Biologi dan Aplikasinya, 2022)
Homalomena pexa, a tomentose haired-leaf aroid, was a newly discovered and described plant species in early 2020. This species has currently only been reported from South Tapanuli. A molecular study to provide DNA sequence is essential in this preliminary investigation. This research aimed to characterize the barcode sequence of H. pexa and estimate the species' position in an Araceae phylogenetic tree. This research used ITS sequence to perform DNA barcoding on H. pexa. The sequencing result revealed that 1040 bp nucleotides were effectively amplified. The phylogenetic tree generated using the Neighbor-Joining method and the Kimura 2-parameter revealed that H. pexa clustered with H. atrox and H. humilis, with a bootstrap value of 97%. This investigation provided and demonstrated that ITS sequences could be used to validate and support the proper identification of Araceae species.